J. LEE NICHOLSON: PIONEER COST ACCOUNTANT. - Hein, Leonard W. (The Accounting Review, 1959)
This article focuses on Major J. Lee Nicholson who was looked upon in the U.S. as the father of cost accounting. Accounting is by no means a new profession. There is evidence that men kept accounts as far back as we are able to find evidence of man's ability to write. One can hardly doubt that he kept some kind of mental accounts even before that. But accounting as a profession in its modern sense is relatively young. Many of its traditions have been developed within the life span of men yet living. Accounting is a profession in ferment. Within this same life span its activity has gone from that of the mere keeper of books to that of an honored authority on the entire business sphere. Where it shall be after the next life span is anyone's guess. Major Nicholson was born in Trenton, New Jersey, in 1863, but spent his early life in Pittsburgh, Pennsylvania. Because of ill-health, he "retired" to California for the last two years of his life, he died in San Francisco on November 2, 1924.